Effect of Mg interlayer on the microstructure and mechanical performance of resistance rivet welded 2 mm Al and ultra-high strength steel - Luyao Kong; Sizhe Niu; Ming Lou; Zixuan Chen; Yunwu Ma; Yongbing Li; Haiyang Lei (Journal of Materials Research and Technology)
Resistance rivet welding (RRW) using semi-tubular rivet was employed to join 2 mm thick AA6061 T6 Al alloy and ultra-high strength steel (UHSS). The influence of a Mg interlayer on the evolution of joint microstructure, mechanical performance and fracture characteristics were thoroughly investigated. The presence of Mg interlayer has negligible impact on the mixed nugget size; however, it significantly alters the joint microstructure. The nugget microstructure is composed of the mixed ferrite and martensite, and the full martensite structure for the RRW joints without and with a Mg interlayer, respectively. The Mg interlayer utilized in RRW plays a significant role in facilitating the formation of martensite. The solidification mechanism of the mixed nugget without the Mg interlayer is governed by the competition between ferrite and austenite stabilized elements. In contrast, for the mixed nugget with the Mg interlayer, the solidification mechanism is primarily influenced by the austenite stabilized elements. Tensile-shear tests reveal that joints with an Mg interlayer predominantly exhibit a button pull-out fracture (BPF) mode, while joints without the Mg interlayer demonstrate the mixed failure modes, including interfacial fracture and BPF. Furthermore, the influence factors including the mixed nugget size, nugget microstructure and load-bearing capacity of the rivet head were analyzed.